7th AIAA Flow Control Conference 2014
DOI: 10.2514/6.2014-2665
|View full text |Cite
|
Sign up to set email alerts
|

Control of Separated Flow on a NACA 0015 Airfoil using Three-Dimensional Plasma Actuator

Abstract: Experimental study has been conducted to determine the effect of a three-dimensional plasma actuator, whose exposed and encapsulated electrodes geometry are designed with serrated configuration, on a NACA 0015 airfoil for flow separation control. The electrodes of the serrated configuration were arranged in a manner that the sawtooth are opposite to each other and horizontally separated by a dielectric material, hence the electrode gap is modified along the spanwise direction. In order to understand the charac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 22 publications
(20 reference statements)
0
1
0
Order By: Relevance
“…Numerous researchers recently deployed alternative electrode configurations to improve the control authority of plasma actuators, as these actuators can induce 3D flow structures, such as plasma synthetic jet and spatially distributed jet, which can postpone/suppress flow separation or excite inherent flow instabilities for effective flow control [14,15]. Among these methods, previous studies reported that plasma actuators using serrated electrode is a promising method with good development potential.…”
Section: Introductionmentioning
confidence: 99%
“…Numerous researchers recently deployed alternative electrode configurations to improve the control authority of plasma actuators, as these actuators can induce 3D flow structures, such as plasma synthetic jet and spatially distributed jet, which can postpone/suppress flow separation or excite inherent flow instabilities for effective flow control [14,15]. Among these methods, previous studies reported that plasma actuators using serrated electrode is a promising method with good development potential.…”
Section: Introductionmentioning
confidence: 99%